Conflict Resolution Strategies In The School Environment, From Teacher And Student Perspectives - Belo Freitas, Joaquina (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
ABSTRACT Conflict resolution is an important aspect of making change and developing students' positive behaviour in the school environment. Therefore, the objective of this research is to understand teachers' perspectives on conflict resolution strategies and teachers' ways of solving problems in the school environment. This scientific study was conducted with a qualitative approach by interviewing respondents such as 1 coordinator, 2 teachers and 2 students. The researcher used thematic analysis to organize the themes that appear frequently in the data. The research results showed that teachers face challenges in the conflict resolution process because teachers use traditional experience to resolve conflict in the school environment. Teachers do not communicate effectively, do not create a positive culture for conflict resolution, do not use problem-solving techniques well. From this result, it is necessary to promote integral and professional training for teachers on effective and efficient conflict resolution strategies. Conflict resolution strategy is a conflict resolution model that involves steps such as open communication and empathy, effective mediation, negotiation and collaboration, using problem-solving techniques, a restorative justice approach, and monitoring results. The implementation of this resolution strategy stage promotes interpersonal relationships between teachers and students in the school environment. The implementation of conflict resolution strategies in the school environment can promote students' positive behaviourist.